Essential oils as alternatives in the control of phytopathogens: A systematic review of the last five years - Marin, Vítor Rodrigues [UNESP]; Zamunér, Caio Felipe Cavicchia [UNESP]; Santos, Eduarda Araújo dos [UNESP]; Ferreira, Henrique [UNESP]; Sass, Daiane Cristina [UNESP] (Taylor & Francis, 2024)
To increase agricultural production and feed the growing human population, the control of phytopathogens, known to affect the quality and yield of fruit and vegetable production, is of utmost importance. Chemical pesticides are by far the most used defensives to control plant diseases, which, despite their effectiveness, are already associated with several health issues in humans, besides their toxic and cumulative effects on the environment and food chain. In this context, natural products appear as viable alternatives to reduce the volume of pesticides used in the field and yet, have a recognized potential to be used in disease management programs. This systematic review highlights the use of essential oils (EOs) as control agents against microbial phytopathogens. Defined as oily, aromatic, and hydrophobic liquids obtained from any part of the plants, EOs are known for their diverse activities, such as antioxidants, anti-inflammatory, antimicrobial, and others. Furthermore, EOs are classified as GRAS (Generally Recognized as Safe) when used as food additives due to their moderate effects on mammals and low persistence in the environment. These characteristics point to EOs as viable alternatives in the research and development of new products and approaches for the control of diseases caused by phytopathogens. The present systematic review reports on scientific novel papers published between January 2019 - June 2023 (approximately five years) that relate the use of EOs against phytopathogens.
Keywords: Antibacterial; Antifungal; Biocontrol; Pesticides; Plant disease